Manitoba First Nations Casino Project : request for proposals - Selection Committee. Manitoba First Nations Casino Project (Manitoba First Nations Casino Project Selection Committee, 2000)
Within a solid framework, First Nations gaming can create opportunities for the host community and adjacent communities, for First Nations people and for the Province of Manitoba as a whole. A sound and practical structure will ensure that benefits from gaming activities accrue to whole communities through the creation of local employment opportunities, the development of spin-off Industries, enhanced tourism projects and the generation of revenues to support community development Initiatives. The purpose of this document is to seek proposals from Manitoba First Nations interested in translating this concept into building opportunities for First Nations people.